Synthesis and properties of 4-(3-amino-2-benzofuranyl)-coumarins - Frasinyuk, Mihaylo; Gorelov, S.; Bondarenko, Svetlana; Khilya, Volodimir (My University, 2009)
The alkylation of o-cyanophenol by 4-chloromethylcoumarins and subsequent intramolecular condensation by the cyano and methylene groups gives substituted 4-(3-amino-2-benzofuranyl) coumarins. We studied the reactions of these compounds with acylating agents as well as with aldehydes, which lead to the 6H-[1]benzofuro[3,2-b]chromeno[4,3-d]pyridin-6-one system as the result of consecutive transformations.
Keywords: кафедра харчової хімії; coumarin; ціанофенол; кумарин; піридин; цианофенол; pyridine